Effect of a 12-month exercise intervention on leukocyte telomere length: Results from the ALPHA Trial. (October 2018) - Friedenreich, Christine M.; Wang, Qinggang; Ting, Nicholas S.; Brenner, Darren R.; Conroy, Shannon M.; McIntyre, John B.; Mickle, Alexis; Courneya, Kerry S.; Beattie, Tara
Highlights: Physical activity decreases cancer risk but the biologic mechanisms are unclear. Leukocyte telomere length was measured before and after a year-long exercise RCT. Average change in telomere length was -13% for exercisers and -8% for controls. Change in telomere length was not significantly different between groups. No effect modification by baseline telomere length, age, obesity, or fitness. Abstract: Background: Short telomeres may indicate a higher risk of cancer and other chronic diseases. Some observational studies show positive associations between leukocyte telomere length (LTL) and physical activity levels. We hypothesized, therefore, that exercise may be one strategy for slowing telomere attrition. Methods: We conducted an ancillary analysis of blood from a year-long, two-centred, two-armed (1:1) randomized controlled trial of aerobic exercise versus usual inactivity. The analysis included 212 physically inactive, disease-free, non-smoking, postmenopausal women (n = 99 exercisers, n = 113 controls) in Alberta, Canada (2003–2006). The exercise prescription was aerobic exercise five days/week (supervised three days/week), 45 min/session, achieving 70–80% heart rate reserve. Baseline and 12-month LTL were analyzed using quantitative real-time polymerase chain reactions (qPCR). The primary statistical analysis was intention-to-treat, comparing the ratio of mean LTLs (12-months:baseline) for exercisers versus controls from a general linear model. Secondary analyses included a per-protocol analysis (≥90% adherence) and analyses stratified by baseline LTL, age, body mass index, and fitness level, respectively. Results: Participants were overweight at baseline (mean BMI = 29 kg/m 2 ). The primary analysis showed no evidence that LTL change differed between groups (12-month mean LTL change for the exercise group: −13% (95% CI: −32%, 11%) versus controls: −8% (95%CI: −27%, 15%); treatment effect ratio (TER, Exercise/Control) = 0.95 (95% CI: 0.68, 1.32). Per-protocol results were similar (TER = 0.87, 95% CI: 0.59, 1.30). In stratified models, TERs ranged from 0.68 to 1.35 across strata and P -interaction > 0.05). Conclusion: We found no evidence to suggest that one year of aerobic exercise alters telomere attrition significantly in healthy postmenopausal women.